Coherence of temperature and velocity superstructures in turbulent Rayleigh–Bénard flow. (25th March 2020) - Krug, Dominik; Lohse, Detlef; Stevens, Richard J. A. M.
Abstract : Abstract : We investigate the interplay between large-scale patterns, so-called superstructures, in the fluctuation fields of temperature [STIX]x1D703 and vertical velocity w in turbulent Rayleigh–Bénard convection at large aspect ratios. Earlier studies suggested that velocity superstructures were smaller than their thermal counterparts in the centre of the domain. However, a scale-by-scale analysis of the correlation between the two fields employing the linear coherence spectrum reveals that superstructures of the same size exist in both fields, which are almost perfectly correlated. The issue is further clarified by the observation that, in contrast to the temperature, and unlike assumed previously, superstructures in the vertical-velocity field do not result in a peak in the power spectrum of w . The origin of this difference is traced back to the production terms of the [STIX]x1D703 and w variance. These results are confirmed for a range of Rayleigh numbers Ra=10^5-10^9 ; the superstructure size is seen to increase monotonically with Ra . Furthermore, the scale distribution of the temperature fluctuations in particular is pronouncedly bimodal. In addition to the large-scale peak caused by the superstructures, there exists a strong small-scale peak. This 'inner peak' is most intense at a distance of [STIX]x1D6FF_[STIX]x1D703 from the wall and is associated with structures of size ≈10[STIX]x1D6FF_[STIX]x1D703, where [STIX]x1D6FF_[STIX]x1D703 is the thermal boundary layer thickness. Finally, based on the vertical coherence relative to a reference height of [STIX]x1D6FF_[STIX]x1D703, a self-similar structure is identified in the velocity field (vertical and horizontal components) but not in the temperature.